Heparin-Based Polyelectrolyte Complex Enhances the Therapeutic Efficacy of Bone Morphogenetic Protein-2 for Posterolateral Fusion in a Large Animal Model. Issue 15 (1st August 2016) - Wang, Ming; Lam, Raymond W.M.; Abbah, Sunny A.; Hu, Tao; Toh, Soo Y.; Cool, Simon; Bhakoo, Kishore; Li, Jun; Goh, James C.H.; Wong, Hee-Kit
Abstract : Study Design: The study was based on porcine posterolateral fusion model. Objective: The study aims to prove that polyelectrolyte complex (PEC) carrier could enhance the efficacy and safety profile of bone morphogenetic protein-2 (BMP-2). Summary of Background Data: BMP-2 was introduced to enhance posterolateral fusion; however, extremely high doses of this molecule were often used which contributed to various complications. This was attributed to the poor modulation capacity of the traditional carrier absorbable collagen sponge (ACS). To reduce the efficacious dose of BMP-2 and its associated complications, heparin-based PEC was introduced. Methods: L3/L4 and L5/L6 two-level posterolateral spinal fusion was performed on six pigs using two doses of BMP-2 with PEC or ACS: (1) PEC with 800 μg BMP-2 (n = 2); (2) PEC with 400 μg BMP-2 (n = 2); (3) ACS with 800 μg BMP-2 (n = 1); (4) ACS with 400 μg of BMP-2 (n = 1). The construct was loaded into a rigid bioabsorbable cage for implantation. Fusion rate and quality were assessed 2 months after operation. Results: Manual palpation revealed successful fusion in all groups. Radiological fusion score of PEC groups was, however, higher than that of ACS groups. The newly formed bone in PEC groups appeared to be well integrated into the native bone with no overgrowth into the adjacent structure. On comparison, in ACS groups, large gaps were observed between the newly formed bone and the fusion bed with heterotopic ossification into the psoas muscle. The microarchitecture on the newly formed bone in PEC groups was superior to that in ACS groups, which was demonstrated by higher three-dimensional parameters. Conclusion: The present study demonstrated that BMP-2 delivered by PEC induced successful posterolateral fusion in porcine model. The efficacy of BMP-2 was improved and bony overgrowth was reduced. The microarchitecture of BMP-2–induced bone tissue was also enhanced by PEC. Level of Evidence: N/A